2017
DOI: 10.1007/s11195-017-9502-z
|View full text |Cite
|
Sign up to set email alerts
|

Views and Experiences of People with Intellectual Disabilities Regarding Intimate Relationships: A Qualitative Metasynthesis

Abstract: The aims of this review were to systematically identify, critically appraise and synthesize the results of existing qualitative literature exploring the views and experiences of intimate relationships amongst people with intellectual disabilities. Fourteen peer-reviewed articles were identified through a systematic search of eight databases, reference lists, citations, and relevant journals. The identified articles were appraised for quality, then synthesized using a metaethnography approach. No study met all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 61 publications
(263 reference statements)
5
42
0
Order By: Relevance
“…In this specific context, perceptions of and concerns for accountability permeate these experiences. In keeping with the results of a previous study (English et al, ), this study reveals that support workers hesitate to offer sociosexual advice and support to service users and that this hesitation upholds professional boundaries between support workers and sexuality specialists. The results of this study further suggest that when interventions are planned to meet service users' needs, they are sometimes mitigated by a precautionary principle.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this specific context, perceptions of and concerns for accountability permeate these experiences. In keeping with the results of a previous study (English et al, ), this study reveals that support workers hesitate to offer sociosexual advice and support to service users and that this hesitation upholds professional boundaries between support workers and sexuality specialists. The results of this study further suggest that when interventions are planned to meet service users' needs, they are sometimes mitigated by a precautionary principle.…”
Section: Discussionsupporting
confidence: 88%
“…A recent metasynthesis concluded that, in the context of physical intimacy, “[…] varying degrees of constraint were being put on [participants] in terms of being able (or allowed) to engage in intimate relationships and to what extent. The prohibition of relationships experienced ranged from the implicit […] to the overtly explicit […]” (English, Tickle, & dasNair, , p. 168).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the experiences of sexuality from the perspective of individuals with IDD is critical to creating accessible and appropriate sexual health education and service (Bernert, 2011). There is a strong need for research that listens to the voices and experiences of self-advocates with IDD, to ensure adaptations to sexuality education are most impactful for this population (English, Tickle, & dasNair, 2018;Whittle & Butler, 2018).…”
Section: Microsystem and Mesosytem Sexual Abuse Risk Factorsmentioning
confidence: 99%
“…As with the typically developing, people with ID want meaningful relationships and desire sexual intimacy and to be sexually active [ 24 ]. As young adults with ID transition from child to adult services tensions are evident regarding the expression of their sexuality due to concerns regarding the risks associated with exploitation versus the right to experience relationships and intimacy [ 25 , 26 ]. However, concerns exist around an individual’s lack of knowledge about relationships and appropriate sexual behaviours [ 27 ].…”
Section: Introductionmentioning
confidence: 99%